2013
DOI: 10.1177/0300985813476066
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Findings in Young and Adult Sheep Following Experimental Infection With 2 Different Doses of Mycobacterium avium Subspecies paratuberculosis

Abstract: Mycobacterium avium subsp paratuberculosis (Map) is assumed to infect young ruminants; however, little is known concerning the possibility of adult animals becoming infected. An experimental infection was conducted to establish the effect of age and doses of Map on susceptibility to paratuberculosis in sheep. Sixteen of twenty-four 1.5-month-old Churra lambs and 23 of 30 adult ewes (from 2-11 years old) were orally challenged with an ovine field strain of Map. Thirteen ewes and 8 lambs were infected with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 37 publications
11
41
1
1
Order By: Relevance
“…Thus, from our results, it can be hypothesized that infection induced by C-type strains could have reached its highest development around 150 dpi, but infected lambs were able to mount a more efficient and specialized immunologic response that would have caused a regression of the lesions. A similar mechanism has been proposed to occur in adult ewes or cows infected with Map showing a higher resistance to infection [27,28,33]. It might have been interesting to have followed these animals over a more uniform and longer timescale such as culling every two months after infection for a longer period.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Thus, from our results, it can be hypothesized that infection induced by C-type strains could have reached its highest development around 150 dpi, but infected lambs were able to mount a more efficient and specialized immunologic response that would have caused a regression of the lesions. A similar mechanism has been proposed to occur in adult ewes or cows infected with Map showing a higher resistance to infection [27,28,33]. It might have been interesting to have followed these animals over a more uniform and longer timescale such as culling every two months after infection for a longer period.…”
Section: Discussionmentioning
confidence: 64%
“…Some of the lambs infected with C-type strains, at 150 dpi showed diffuse lesions affecting wide areas of intestinal mucosa not associated with the lymphoid tissue, which has been regarded as related to more advanced stages of Map infection [4-6,23,28,29]. According to the pathological findings at 390 dpi, lesions induced by C strains in sheep showed an evolution towards resolution, with a marked decrease in their severity, characterized by lower numbers of smaller, well-encapsulated and fibrotic granulomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,11,18 This study has shown that macrophages present in the granulomatous infiltrates show different immunohistochemical expression of the markers examined, as seen by the differences in the H-scores for several of these markers, depending on the lesion type. These differences can probably play different roles in their development.…”
Section: Discussionmentioning
confidence: 79%